A facile reduction treatment to derive Mo6S8 from exfoliated MoS2 for efficient microwave absorption applications. (15th May 2019) - Sun, Yuan; Xu, Wei; Hou, Wentao; Wang, Yuanqi; Wang, Tingting; Wu, Liqian; Xu, Xiaobing; Zhang, Yu; Zhou, Xuan; Du, Youwei; Zhong, Wei
Abstract: Here, we report a facile one-step fabrication route by thermal treatment of exfoliated MoS2 . At the presence of hydrogen, Mo6 S8 with great crystallinity was synthesized via thermal reduction of exfoliated MoS2 at 900 °C. The corresponding mechanisms were discussed experimentally and theoretically. The electromagnetic properties and microwave attenuation performances of Chevrel Phase Mo6 S8 and its heterostructures with MoS2 were investigated for the first time. Results illustrated that considerable microwave absorptions were achieved in Mo6 S8 and Mo6 S8 /MoS2 hybrid structure which possessed suitable impedance matching ratio and strong dielectric loss. The minimum reflection loss reached −38.1 dB for Mo6 S8 and −47.5 dB for Mo6 S8 /MoS2 heterostructure, which were significantly enhanced compared to bare MoS2 . The exhibiting results suggest that Chevrel Phase and its hybrid with MoS2 are promising microwave absorbing materials, which opens a new pathway for the applications of Chevrel Phase.